2019
DOI: 10.1016/j.jmb.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Analysis of HIV-1 Fusion Inhibition Using Small gp41 Mimetic Proteins

Abstract: Development of effective inhibitors of the fusion between HIV-1 and the host cell membrane mediated by gp41 continues to be a grand challenge due to an incomplete understanding of the molecular and mechanistic details of the fusion process. We previously developed singlechain, chimeric proteins (named covNHR) that accurately mimic the N-heptad repeat (NHR) region of gp41 in a highly stable coiled-coil conformation. These molecules bind strongly to peptides derived from the gp41 C-heptad repeat (CHR) and are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 70 publications
(51 reference statements)
5
43
0
Order By: Relevance
“…Recently, we have designed, produced and characterized several protein molecules that mimic the structure of the NHR helices trimer of the intermediate state of fusion of gp41 [25,26]. These proteins, called covNHR, consist of a single polypeptide chain with three helical regions that fold as a trimeric bundle with a structure highly similar to the NHR gp41 region.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have designed, produced and characterized several protein molecules that mimic the structure of the NHR helices trimer of the intermediate state of fusion of gp41 [25,26]. These proteins, called covNHR, consist of a single polypeptide chain with three helical regions that fold as a trimeric bundle with a structure highly similar to the NHR gp41 region.…”
Section: Introductionmentioning
confidence: 99%
“…They are also very stable and highly soluble. We have shown that covNHR molecules bind with high affinity to peptides derived from the CHR region of gp41 and neutralize HIV cell infection with high potency (IC 50 in the low nanomolar range) for a wide variety of HIV strains and even for T20-resistant variants [26].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations